Utilisation of wheat bran as a substrate for bioethanol production using recombinant cellulases and amylolytic yeast. (15th December 2015) - Cripwell, Rosemary; Favaro, Lorenzo; Rose, Shaunita H.; Basaglia, Marina; Cagnin, Lorenzo; Casella, Sergio; van Zyl, Willem
Highlights: A cocktail of recombinant cellulases was proposed for wheat bran hydrolysis. Optimal conditions for enzymatic hydrolysis of wheat bran were determined. Recombinant amylolytic strains completely hydrolysed the starch in wheat bran. Addition of cellulases to SSF with amylolytic strains enhanced ethanol yield. Abstract: Wheat bran, generated from the milling of wheat, represents a promising feedstock for the production of bioethanol. This substrate consists of three main components: starch, hemicellulose and cellulose. The optimal conditions for wheat bran hydrolysis have been determined using a recombinant cellulase cocktail (RCC), which contains two cellobiohydrolases, an endoglucanase and a β-glucosidase. The 10% (w/v, expressed in terms of dry matter) substrate loading yielded the most glucose, while the 2% loading gave the best hydrolysis efficiency (degree of saccharification) using unmilled wheat bran. The ethanol production of two industrial amylolytic Saccharomyces cerevisiae strains, MEL2[TLG1-SFA1] and M2n[TLG1-SFA1], were compared in a simultaneous saccharification and fermentation (SSF) for 10% wheat bran loading with or without the supplementation of optimised RCC. The recombinant yeast S . cerevisiae MEL2[TLG1-SFA1] and M2n[TLG1-SFA1] completely hydrolysed wheat bran's starch producing similar amounts of ethanol (5.3 ± 0.14 g/L and 5.0 ± 0.09 g/L, respectively). Supplementing SSF with RCC resulted in additional ethanol production of about 2.0 g/L. Scanning electron microscopy confirmed the effectiveness of both RCC and engineered amylolytic strains in terms of cellulose and starch depolymerisation. This study demonstrated that untreated wheat bran could be a promising ready-to-use substrate for ethanol production. The addition of crude recombinant cellulases improved ethanol yields in the SSF process and S . cerevisiae MEL2[TLG1-SFA1] and M2n[TLG1-SFA1] strains can efficiently convert wheat bran's starch to ethanol.